(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and histopathological characteristics and BRCA1/2 mutation profiles in breast cancer patients treated at Nghe An Oncology Hospital. Methods: A cross-sectional descriptive study with analytical components was conducted among 373 breast cancer patients treated at Nghe An Oncology Hospital between 2024 and 2025. High-risk patients underwent next-generation sequencing (NGS) to identify BRCA1/2 mutations. Results: Tumors were more frequently located in the right breast (52.55%), with the upper outer quadrant being the most common tumor location (56.3%). Stage II disease accounted for the largest proportion of cases (54.4%). Invasive ductal carcinoma was the predominant histopathological type (83.9%), and histological grade II accounted for the majority of cases (77.47%). Luminal B/HER2-negative was the most common molecular subtype. BRCA1/2 genetic analysis identified pathogenic or likely pathogenic (P/LP) variants in 10 high-risk patients (9.7%), including four patients (3.9%) with BRCA1 variants and six (5.8%) with BRCA2 variants. The most frequently detected mutation was NM_000059.4:c.6490C>T (p.Gln2164Ter), located in exon 11 of BRCA2. The P/LP variants identified in BRCA1 and BRCA2 were protein-truncating variants that were expected to affect the structure or function of the BRCA1/2 proteins. These variants were supported by strong evidence of pathogenicity according to the ACMG/AMP criteria, including PVS1 and PM2, and had been reported in ClinVar with multiple submissions or previously classified as pathogenic. Conclusions: Breast cancer patients treated at Nghe An Oncology Hospital were predominantly diagnosed with stage II disease, and invasive ductal carcinoma was the most common histopathological type. Among 103 high-risk patients who underwent genetic testing, 10 (9.7%) carried P/LP variants in BRCA1/2, including four patients with BRCA1 variants and six with BRCA2 variants.